A review of modelling high pH stress corrosion cracking of high pressure gas pipelines. Issue 3 (28th September 2015) - Griggs, J.; Gamboa, E.; Lavigne, O.
Abstract : Modelling of intergranular stress corrosion cracking (SCC) in pipelines is an important field of study as predictive techniques are integral to pipeline integrity and management. An inclination of the SCC propagation direction has been observed for some pipelines, which is not predictable using existing models as they assume perpendicular crack growth. A review has been conducted to identify the applicable techniques from existing models, as well as the gaps in current knowledge. Existing work in crack growth rates, stress formulations and microstructural representations are reviewed. Mechanical dependency of the electrochemical response is identified as a gap and proposed for inclusion in a model alongside the other areas reviewed.